Risk Assessment of Red Cell Transfusion in Congenital Heart Disease - Zürn, Christoph; Höhn, René; Hübner, David; Umhau, Markus; Kroll, Johannes; Kari, Fabian A.; Humburger, Frank; Maier, Sven; Stiller, Brigitte (The Thoracic and Cardiovascular Surgeon, 2022)
Background The storage time of packed red blood cells (pRBC) is an indicator of change in the product's pH, potassium, and lactate levels. Blood–gas analysis is a readily available bedside tool on every intensive care ward to measure these factors prior to application, thus facilitating a calculated decision on a transfusion's quantity and duration.Our first goal is to assess the impact of storage time on pH, potassium, and lactate levels in pRBC. The influence of those parameters in the transfused children will then be evaluated.Methods In this retrospective study, we conducted blood–gas analyses of pRBC units before they were administered over 4 hours to neonates, infants, and children in our pediatric cardiac intensive care ward. All patients underwent regular blood–gas analyses themselves, before and after transfusion.Results We observed a highly significant correlation between the storage time of pRBC units and a drop in pH, as well as an increase in potassium and lactate of stored red cells (p< 0.0001). Median age of recipients with a complete blood–gas dataset was 0.1 (interquartile range [IQR] = 0.0–0.7) years; median pRBC storage duration was 6 (IQR = 5–8) days. Further analyses showed no statistically significant effect on children's blood gases within 4 hours after transfusion, even after stratifying for pRBC storage time ≤7 days and >7 days.Conclusion Stored red blood cells show a rapid decrease in pH and increase in potassium and lactate. Slow transfusion of these units had no adverse effects on the recipients' pH, potassium, and lactate levels.
Keywords: blood transfusion; congenital heart disease; intensive care; neonate; pediatric